Teaching interprofessional collaboration among future healthcare professionals - Kauff, Mathias; Bührmann, Thorsten; Gölz, Friederike; Simon, Liane; Lüers, Georg; van Kampen, Simone; Kraus de Camargo, Olaf; Snyman, Stefanus; Wulfhorst, Britta (Frontiers in Psychology, 2023)
Healthcare has become more complex in recent years. Such complexity can best be addressed by interprofessional teams. We argue that to ensure successful communication and cooperation in interprofessional teams, it is important to establish interprofessional education in health-related study programs. More precisely, we argue that students in health-related programs need to develop interprofessional competencies and a common language, experience interprofessional contact, build inclusive identities and establish beliefs in the benefit of interprofessional diversity. We give examples how these goals can be implemented in interprofessional education. We also discuss challenges and future avenues for respective research.